2001
DOI: 10.1159/000046253
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Massive Lower Gastrointestinal Bleeding Caused by Mixed Infection of Cytomegalovirus and Mucormycosis in a Renal Transplant Recipient

Abstract: We describe a case of lower gastrointestinal bleeding due to mixed infection of cytomegalovirus (CMV) and mucormycosis in a renal transplant recipient. A 33-year-old male received renal transplantation and his clinical course was uneventful. On the 18th postoperative day, acute rejection was developed and this was treated with high-dose methylprednisolone and OKT3. During antirejection treatment, sudden onset massive hematochezia was developed. Emergency colonofibroscopy revealed multiple colonic ulcers and pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 6 publications
1
25
0
Order By: Relevance
“…Cytomegalovirus (CMV) colitis is a common cause of life‐threatening opportunistic viral infection, especially in immunocompromised patients such as transplant recipients and HIV‐infected patients 1–4 . Cytomegalovirus infections are generally asymptomatic in healthy adults, but CMV infection in immunocompromised host has very serious and fatal clinical outcomes 5 …”
Section: Introductionmentioning
confidence: 99%
“…Cytomegalovirus (CMV) colitis is a common cause of life‐threatening opportunistic viral infection, especially in immunocompromised patients such as transplant recipients and HIV‐infected patients 1–4 . Cytomegalovirus infections are generally asymptomatic in healthy adults, but CMV infection in immunocompromised host has very serious and fatal clinical outcomes 5 …”
Section: Introductionmentioning
confidence: 99%
“…One was caused by a mixed infection of mucormycosis with cytomegalovirus in a renal transplant patient [11]. Anand et al, [6] reported a similar case of bleeding from colonic mucormycosis from our institution.…”
Section: Discussionmentioning
confidence: 99%
“…Direct penetration and growth through the blood vessel wall explain the propensity for thrombosis and tissue necrosis, the two major hallmarks of this disease (1). The risk factors associated with zygomycosis are diabetes with acidosis, immunocompromised status, renal failure, recent gastrointestinal surgeries, intraoperative blood transfusions, bacterial infection with prolonged antibiotic therapy, and cytomegalovirus infection (1,(4)(5)(6). There is enough evidence to suggest that in patients with chronic renal failure requiring dialysis, deferoxamine therapy may be an important corisk factor, as Zygomycetes are able to utilize iron bound to iron chelators to enhance their growth (6,7).…”
Section: Discussionmentioning
confidence: 99%